POSSIBILITIES OF IVABRADINE, A SELECTIVE INHIBITOR OF ION F-CHANNELS OF SINUS NODE, IN PREVENTION OF ANTHRACYCLINE CARDIOTOXICITY IN PATIENTS WITH BREAST CANCER - Yu. V. Vasyuk; V. V. Nesvetov; E. L. Shkolnik; L. D. Shkolnik; G. V. Varlan; G. E. Gendlin; E. I. Emelina (Рациональная фармакотерапия в кардиологии)
Aim. To study the efficacy of ivabradine in the prevention of cardiotoxic effects due to chemotherapeutic drugs in patients with breast cancer. Material and methods. The open randomized uncontrolled study included 55 patients with breast cancer who had to undergo chemotherapy by anthracyclines. The inclusion criterion was a heart rate >70 beats/min. Collection of complaints and anamnesis, ECG, echocardiography, routine laboratory tests were performed in all patients initially and after 1, 3, 6 and 12 months. All patients were treated with polychemotherapy with anthracyclines in combination with cyclophosphamide and fluorouracil. The patients included into the study were randomized into two groups. Patients of the main group (n=23) were additionally prescribed ivabradine in a daily dose of 10 mg followed by a dose titration. Patients of the control group (n=32) received only polychemotherapy. Results. In the main group a decrease in heart rate was observed already by the first month (from 83.6±9.5 to 67.1±7.5 beats/min, p<0.001) and persisted until the 6th month (74.2±14.9 beats/min, p<0.001). In the main group, the frequency of complaints of palpitation significantly decreased by the 1st month of treatment (from 60.9% to 30%, p=0.05) with a slight increase in further observation. A significant increase in the left atrium diameter (from 35.0±4.0 to 35.9±3.9 cm; p=0.009), the left atrium volume (from 42.0±12.8 to 43.7±11.6 ml; p=0.02), the end diastolic left ventricle (LV) volume (from 81.5±16.5 to 88.8±16.5 ml, p=0.007) and the end systolic LV volume (from 30.7±8.1 to 32.3±6.2 ml; p=0.01) were found in the main group in a month after polychemotherapy. Dynamics of the main echocardiographic indices was similar in the control group. By 6 months of observation the indexed mass of LV myocardium significantly increased in the control group (from 66.9±14.6 to 74.3±19.0 g/m2; p=0.024) in the absence of that in the main group (from 65.4±15.2 to 70.7±11.3 g/m2; p>0.05). A significant change in the LV ejection fraction was not found in both groups. Significant differences in LV global longitudinal strain were found between groups in 1, 3 and 6 months of observation (p<0.05), but after 12 months the groups were comparable in longitudinal strain values. Conclusion. Ivabradine therapy in patients with breast cancer and heart rate >70 beats/min was safe and did not cause bradycardia. Ivabradine use was accompanied by a significant reduction in a number of patients with complaints of palpitation, contributed to the preservation of normalLV global longitudinal deformation in chemotherapy, while the control group had negative changes with a maximum by the 6th month of follow-up.